Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Somebody divided $\frac{cx+d}{ax+b}$ into $$ \frac{c}{a} + \frac{d- \frac{bc}{a}}{ax+b} .$$ For use for integrals.

Does anybody knows how was it done? Could you show me how to do something like that, please?

Thanks in advance.

share|cite|improve this question
up vote 7 down vote accepted

It's polynomial long division. In this relatively simple case (first degree polynomials in both numerator and denominator) you can also do it like this, using an "add-and-subtract" trick: $$ \frac{cx+d}{ax+b} = \frac{c(x + d/c)}{a(x+b/a)} = \frac{c}{a} \frac{(x+b/a)+(d/c-b/a)}{x+b/a} = \frac{c}{a} \left( 1 + \frac{d/c-b/a}{x+b/a} \right).$$

share|cite|improve this answer

It is the linear case of the polynomial remainder theorem: $\rm\ f(x)\ \ mod\ \ a\:x + b\ =\ f(-b/a)\:.\ $ This has a very simple proof. Namely, by the division algorithm for polynomials over a field, $\rm\ f(x)\ =\ (a\ x + b)\ q(x) + r\ $ so $\rm\ r = f\:(-b/a)\ $ follows by evaluation at $\rm\ x = -b/a\:.\ $ In your case $\rm\ f(x)\ =\ c\ x + d\ $ so $\rm\ r = f\:(-b/a) = d - bc/a\:.\ $ Also, comparing degrees shows that the quotient has degree zero $\rm\:q(x) = q\:.\ $ Comparing leading coefficients yields $\rm\ c = a\ q\ $ so $\rm\ q(x) = q = c/a\:.\ $

Hence $\rm\displaystyle\quad c\ x + d\ =\ (a\ x + b)\ q + r\ \ \Rightarrow\ \ \frac{c\ x + d}{a\ x + b}\ =\ q + \frac{r}{a\ x + b},\quad q = \frac{c}a,\ \ r = d-\frac{bc}a$

More generally, over any Euclidean domain, i.e. any integral domain with a division algorithm, one may use the division algorithm to decompose a fraction into an integral and fractional part. This is frequently the inlined $\:$ descent $\: $ step in proofs that implicitly invoke unique factorization.$\ $ For example, see my analysis of a proof of square-root irrationality presented by John Conway.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.